Pengaruh Citra Merek dan Gaya Hidup Terhadap Keputusan Pembelian Produk Eiger (Jurnal Manajemen dan Investasi (MANIVESTASI), 2021)
ABSTRACTThe problem in this research is whether there is an influence of brand image and lifestyle partially or simultaneously (simultaneously) on the purchase decision of Eiger products. The purpose of this study was to determine the effect of brand image and lifestyle partially or jointly on the purchase decision of Eiger products. The problem limitation in this research is the Eiger store in Seberang Ulu II, Palembang city. The method used in this research is quantitative method. Data collection techniques were carried out by observation and questionnaire questionnaire. Data analysis techniques used are classical assumption tests, multiple linear regression, hypothesis testing, correlation coefficient tests and coefficient of determination tests. Based on the research results, it can be seen that 1) there is no partially significant effect of brand image on purchasing decisions for Eiger products. This is evidenced by the value of tcount ttable of 8.761> 1.660 with a significant value of 0.000